Drugs and your friends - Hurwitz, Sue, 1934-; Shniderman, Nancy, 1956- (New York : Rosen Pub. Group, 1992)
Discusses peer pressure and drug use and the importance of making the right choice.
Includes bibliographical references (p. 60-61) and index.
7-10.
Keywords: Children -- Alcohol use -- United States -- Juvenile literature; Children -- Drug use -- United States -- Juvenile literature; Teenagers -- Alcohol use -- United States -- Juvenile literature; Teenagers -- Drug use -- United States -- Juvenile literature; Drug abuse; Substance abuse